Interaksi Sosial Mahasiswa Pendidikan Jasmani, Kesehatan dan Rekreasi (PJKR) FKIP Universitas Palangka Raya di Masa Pandemi Covid-19 - Mikdar Mikdar; Zuly Daima Ulfa; Andi Tenri Abeng (Litbang PWM Jawa Tengah, 2021)
Pandemic covid-19 has an impact in the implementation of daily activities including on students. Social distancing is carried out in order to prevent the transmission of covid-19. Outdoor activities are restricted, requiring adjustments including social interactions. This study aims to identify the social interaction of students of Physical Education, Health and Recreation (PJKR) FKIP University of Palangka Raya during the covid-19 pandemic. Research is a survey with a crosssectional approach in students PJKR study program, FKIP University of Palangka Raya, as many as 115 people. Sampling technique used is simple random sampling. Online data collection using questionnaires through google form. Social interaction between students related to assignments and lecture activities (88%), communication outside campus activities (45%), student and extracurricular activities (34%), hobbies and achievements (33%). While the social interaction of students with lecturers related to lecture materials (91%), lecture assignments (64%), academic guidance activities (20%), off-campus activities (14%) and other interactions. Changes in social interaction in the form of interactions become limited, online communication increases including the utilization of social media as well as increased use of mobile phones and other devices. Advice should be considered concern about lecture activities that involve social interaction between students, students with lecturers and students with the community and the use of technology while maintaining the prevailing social values in the community.